Highly sensitised individuals present a distinct Treg signature compared to unsensitised individuals on haemodialysis - Dudreuilh, C.; Basu, S.; Shaw, O.; Burton, H.; Mamode, N.; Harris, F.; Tree, T.; Nedyalko, P.; Terranova-Barberio, M.; Lombardi, G.; Scottà, C.; Dorling, A. (Frontiers in Transplantation, 2023)
Highly sensitised (HS) patients represent up to 30% of patients on the kidney transplant waiting list. When they are transplanted, they have a high risk of acute/chronic rejection and long-term allograft loss. Regulatory T cells (Tregs) (CD4+CD25hiCD127lo) are T cells involved in suppression of immune alloresponses. A particular subset, called T follicular regulatory T cells (Tfr, CXCR5+Bcl-6+) is involved in regulating interactions between T effectors and B cells within the germinal centre and can be found in peripheral blood. Therefore, we wanted to identify specific subsets of Tregs in the peripheral blood of highly sensitised individuals. We recruited prospectively healthy volunteers (HV) (n=9), non-sensitised patients on hemodialysis (HD) (n=9) and highly sensitised (HS) individuals, all of whom were on hemodialysis (n=15). We compared the Treg phenotypes of HV, HD and HS. HS patients had more CD161+ Tregs (p=0.02), more CD45RA-CCR7- Teffectors (Teffs) (p=0.04, memory Teffs able to home to the germinal centre) compared to HV. HS had more Bcl-6+ Tregs (p<0.05), fewer Th1-like Tregs, more Th2-like Tregs (p<0.001), more CD161+ (p<0.05) Tregs compared to HD patients. This population has been described to be highly suppressive. HD had a deficiency in a Th17-like CD161+ effector Treg cluster (cluster iii., CCR6+CCR4+CXCR3- CD39+CD15s+ICOS-CCR7-CD161+) (p<0.05). This is the first study presenting a deep Treg phenotype in HS patients. We confirmed that HS patients had more of a Th17-like CD161+ effector Tregs from population III (CD4+CD25hiCD127loCD45RA-) compared to unsensitised HD. The clinical relevance of this highly suppressive Tregs population remains to be determined in the context of transplantation.